Gambaran kebutuhan perawatan ortodonti berdasarkan indikator kebutuhan perawatan ortodonti (ikpo) (Kajian Pada Remaja Usia 15 – 17 tahun di SMA GITA KIRTTI 3) - Nofrizal, Riko; Auliashinta, Annisa (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Adolescent are often aware of their physical performance and they will find solutions in order to achieve the ideal appearance. The ideal appearance especially on the teeth is an important factor in increasing facial attractiveness which is important in social interactions. There are several important factors that affect the appearance of teeth, including color, shape, and position of the teeth especially the anterior teeth and if there is trauma to the anterior teeth that can be overcome with orthodontic treatment. There is an indicator that can be used to determine the level of need for orthodontic treatment. Objective: The purpose of this study was to determine the orthodontic treatment needs of Gita Kirtti 3 High School students based on the Orthodontic Care Needs Indicator (IKPO). in this study there were 51 subjects aged 15-17 years who were determined as research subject. The subject then filled out the IKPO questionnaire that had been given. Results: The results of this study showed that based on the IKPO score, 45 subjects (88.2%) need orthodontic treatment and 6 subjects (11.8%) did not need orthodontic treatment. Based on the distribution of gender, both men and women have more scores who need orthodontic treatment than those who do not need orthodontic treatment. Conclusion: From this study, it can be concluded that the number of orthodontic treatment needs in Gita Kirtti 3 high school students is high, this shows that adolescent knowledge and awareness of orthodontic treatment is good enough so that the level of willingness to undergo orthodontic treatment is so high.